mTOR and ROS regulation by anethole on adipogenic differentiation in human mesenchymal stem cells - Rhee, Yun-Hee (BMC Cell Biol, 2018)
BACKGROUND: Adipocyte differentiation of human mesenchymal stem cells (hMSCs) is dependent on mitochondrial metabolism and reactive oxygen species (ROS) to initiate adipocyte differentiation. Although anethole has been known as an anti-oxidant and lipid peroxidation inhibitor, there is little investigated about its role in adipogenic differentiation. METHODS: The effects on cytotoxicity and proliferation of anethole in hMSCs were measured by the MTT assay. The anti-adipogenic effect of anethole on hMSCs was analyzed by Oil Red O staining and western blot analysis. The anti-oxidant activity of anethole on hMSC was assessed by flowcytometry and fluorescence staining using 2',7' –dichlorofluorescin diacetate (DCFDA). The western blotting was used to detect of phospho-Akt, phospho-mTOR, phospho-p70S6K, PPARγ, and phsopho-AMP-activated kinase (AMPK). RESULTS: Anethole suppressed the adipogenic differentiation of hMSCs through down-regulation of Akt-mTOR-p70S6K-PPARγ and up-regulation of AMPK. Anethole affected oxidative conditions through ROS generation. Anethole also rescued AMPK activity and reduced activation of mTOR-p70S6K-PPARγ under oxidative conditions in presence of exogenous hydrogen peroxide. CONCLUSION: ROS and mTOR regulation is a crucial factor in adipogenic differentiation, anethole has an important role in regulating activities of mTOR/PPARγ and ROS control in adipogenic differentiation of hMSCs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12860-018-0163-2) contains supplementary material, which is available to authorized users.